CHALLENGES FOR INVESTIGATING ONLINE PROSTITUTION - Sri Setiawati; Sri Hartati (Jurnal Meta-Yuridis, 2023)
Cyber crime is a crime with a computer or computer network being a tool, target or place of crime. Included in cyber crimes include online prostitution. The purpose of writing this article is to find out the police's efforts to investigate online prostitution crimes and what are the obstacles and solutions in conducting online prostitution investigations by the police. This paper uses a normative juridical approach in its preparation. the result of the study conducted is that before the police investigators conduct an investigation, an investigation is carried out to find out and confirm the existence of a criminal act of prostitution through social media; after the minutes of the document are completed and declared complete by the public prosecutor, then P21 proceeds. The obstacle faced by the police is the anonymity of the perpetrator. The solution presented is to coordinate with the provider (communication service provider), the social media service provider and, the Bank